Nilai-nilai Islam dalam Kebudayaan Indonesia (Kajian Filsafat Nilai) - Widyastini Widyastini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Indonesia consisted of many islands tribes, customs, and traditions cultures, and several kinds of religion. Their diversity, line